Immunotoxicity from checkpoint inhibitor therapy: clinical features and underlying mechanisms. Issue 2 (19th November 2019) - Fessas, Petros; Possamai, Lucia A.; Clark, James; Daniels, Ella; Gudd, Cathrin; Mullish, Benjamin H.; Alexander, James L.; Pinato, David J.
Summary: Immune checkpoint inhibition with monoclonal antibodies is becoming increasingly commonplace in cancer medicine, having contributed to a widening of therapeutic options across oncological indications. Disruption of immune tolerance is the key mechanism of action of checkpoint inhibitors and although immune‐related adverse events are a typical class effect of these compounds, the relationship between toxicity and response is not fully understood. Awareness and vigilance are paramount in recognizing potentially life‐threatening toxicities and managing them in a timely manner. In this review article, we provide an overview of the clinical features, pathological findings and management principles of common immune‐related toxicities, attempting to provide mechanistic insight into an increasingly common complication of cancer therapy. Abstract : An overview of the clinical features and management principles of toxicities related to immune checkpoint inhibitors, with a particular focus on current understanding of pathophysiological mechanisms.